(untitled) (Journal of Building and Road Research, 2021)
The paper focuses on comparing the popular daylight simulation softwareresults against the measured on-site data; it investigates softwareaccuracy and its limitations when used to calculate the daylight illuminance in clear sky conditions. The objective of the study is to examine the existence of any discrepancy and identify any systematic trend between actual and predicted results. Petrodar and NTC, both high-rise office buildings in Khartoum, were selected as case studies for the validation purposes. The study concluded that the diffuse daylight was simulated more accurately than the direct component. The variation between the measured values and simulated ones occurs at the points facing direct sunlight, and mostly when the sun comes at a low angle, this variation reached twice the measured in four cases. The study highlights the need for more refinement of the software when simulating direct component of daylight in clear sky conditions.